Madeleine Blais-Dahlem et sa vision de l’autotraduction - Czubińska, Małgorzata (Romanica Silesiana, 2020)
Nowadays self-translation remains a frequent practice in the literary field in Canada. A close reading of the self-translations done by Canadian writers such as Nancy Houston, Marco Micone or Patrice Desbiens allows to discover each author’s own vision of self-translation as a creative process. The aim of the paper is to determine, through a comparative analysis of excerpts from the two language versions of the play La Maculée/sTain (2012) and the latest bilingual novel La voix de mon père / My Father’s Voice (2015) by Fransaskois playwright Madeleine Blais-Dahlem, to what extent her self-translating practice guides the reading of the text. Examining the back and forth between the two versions of the same work will allow to delve deeper into the subject of the identity and privileged status of the translator (Tanqueiro 2009: 109, Saint 2018: 120), but also into the role and skills of the receiver of Madeleine Blais-Dahlem’s bilingual writings.